THE INFLUENCE OF THE QUALITY OF HUMAN RESOURCES IN PUBLIC SERVICES ON COMMUNITY SATISFACTION IN SOLOKAN JERUK DISTRICT, BANDUNG REGENCY - Rahmat Santa; Marcelina Utami Ngesti (STIA Bagasasi, 2022)
The role of human resources in government is a very important element in running the government. Human resource management in government is very important as an effort in the relevance between capabilities and fields that are carried out, so that there is no imbalance between abilities and duties and obligations that must be carried out. The progress or failure of an organization depends on the management or management of human resources. Therefore, existing human resources will affect the achievement of work goals and the response of society. The research was conducted using a quantitative descriptive method. The results of the data collected will be processed numerically and described based on the processed data that has been tested. The research subjects that have been determined are the people around the Solokan Jeruk District, Bandung Regency. The research population taken in this study was 60 people. This study has two variables that are the focus of research, namely the human resource variable (X) and community satisfaction variable (Y). The hypothesis to be tested in this study relates to whether or not there is a significant influence between the independent or independent variables on the dependent or independent variables. The results of this study obtained a score of human resources and community satisfaction in the Good category. These results state that there is an influence of human resources on community satisfaction in Solokan Jeruk District, Bandung Regency.